IMPLEMENTASI THEODOLITE DALAM PENENTUAN ARAH KIBLAT KAMPUS STAIN SULTAN ABDURRAHMAN KEPULAUAN RIAU - M. Arbisora Angkat (Fakultas Syariah Institut Agama Islam Negeri Palu, 2022)
The determination of qibla direction in this era is not only for worship places, but it has become a necessity for certain locations such as restaurants, hotels and offices. About the far distance between Indonesia and Mecca, a more modern tool such as Theodolite is needed to determine the precise qibla direction. Theodolite is a modern tool that has become the national standard for determining qibla direction in Indonesia. Theodolite is an instrument that can determine the qibla direction accurately and precisely because the numbers on this tool show very detailed numbers. This research was conducted because the researcher saw that the direction of STAIN Sultan Abdurrahman Riau Islands college was still predictive, namely by facing west and then tilting to the right slightly. It is necessary to determine the qibla direction of STAIN Sultan Abdurrahman Riau Islands college using modern tools such as the Theodolite to produce a precise qibla direction. After calculating, it is known that the qibla azimuth of STAIN Sultan Abdurrahman Riau Islands college is 293º 03' 35.37